Pseudomembranous colitis in children: Experience of a university hospital in Korea - Jae Hyun Park; Kyung Ji Kang; Yu Na Kang; Ae Suk Kim; Jin-Bok Hwang (Korean Pediatric Society, 2010)
Purpose : Pseudomembranous colitis (PMC) occurs rarely in children, but its incidences are increasing due to frequent antibiotic use. We investigated the incidence and clinical characteristics of PMC accompanied by bacterial enteritis-like symptoms in children. Methods : Between November 2003 and July 2007 at the Department of Pediatrics, Dongsan Medical Center, we analyzed the medical records of consecutive patients who received antibiotics in the past 1 month, developed bacterial enteritis-like symptoms, and were diagnosed with PMC based on sigmoidoscopy examination and histological findings. Results : Among 22 patients who underwent sigmoidoscopy and biopsy examinations, 11 (50%) were diagnosed with PMC. These 11 patients were aged 2 months-12 years, among whom 5 patients (45.5%) were less than 1 year old. The clinical symptoms were bloody diarrhea (28.6%), abdominal pain or colic (28.6%), watery or mucoid diarrhea (23.8%), vomiting (9.5%), and fever (9.5%). The antibiotics used were penicillins (55.6%), macrolides (27.8%), cephalosporins (11.1%), and aminoglycosides (5.6%). The period of antibiotic use was 3-14 days. The interval between the initial antibiotic exposure and the onset of symptoms was 5-21 days. The results of stool examination of all patients were negative for Clostridium difficile toxin A. Patient distribution according to the degree of PMC was as follows: grade I, 18.2% (2 cases); grade II, 27.3% (3); grade III, 36.4% (4); and grade IV, 18.2% (2). PMC did not recur in any case. Conclusion : PMC is not a rare disease in children. If pediatric patients receiving antibiotics manifest symptoms like bacterial enteritis, PMC should be suspected. Endoscopy and biopsy should be applied as aggressive diagnostic approaches to detect this condition.